Continuous measurement of lactate concentration in human subjects through direct electron transfer from enzymes to microneedle electrodes - Freeman,DME; Ming,DK; Wilson,R; Herzog,PL; Schulz,C; Felice,AKG; Chen,Y-C; O'Hare,D; Holmes,AH; Cass,AEG (ACS Sensors, 2023)
Microneedle lactate sensors may be used to continuously measure lactate concentration in the interstitial fluid in a minimally invasive and pain-free manner. First- and second-generation enzymatic sensors produce a redox-active product that is electrochemically sensed at the electrode surface. Direct electron transfer enzymes produce electrons directly as the product of enzymatic action; in this study, a direct electron transfer enzyme specific to lactate has been immobilized onto a microneedle surface to create lactate-sensing devices that function at low applied voltages (0.2 V). These devices have been validated in a small study of human volunteers; lactate concentrations were raised and lowered through physical exercise and subsequent rest. Lactazyme microneedle devices show good agreement with concurrently obtained and analyzed serum lactate levels.